THE TYPICAL INTERPRETATION OF ISLAM NUSANTARA ON PLURALITY OF GUS MUWAFIQ PERSPECTIVE - Rahmat, Rahmat; Fadlurahamn, Muhammad Hammam; Afdhal, Andi muhammad (State Islamic University of Datokarama Palu, 2024)
Situationally and conditionally plural reality in Indonesia is not a new thing, but has long grown and developed and cultured in the archipelago. Something like this should have been exceeded by all of us. However, today, extremist movements are still entrenched which if left unchecked, will have fatal consequences for the nation's sovereignty. This research will discuss the concept of Gus Muwafiq's interpretation with the idea of his understanding in caring for the archipelago, through the approach of historicity and culturality of the archipelago typical of Indonesia. This research is a research with primary sources of Youtube videos and supported by related books and articles. The data in this study was collected by qualitative methods and using a phenomenological approach where the object of the phenomenon was Gus Muwafiq as an interpreter, in the context of answering the challenges of plurality in Indonesia. The results of this study show that Indonesia holds a big concept that comes from Islam itself, namely the concept of raiyyah (people) which is intended to be mutually responsible in building and caring for the nation. This idea is in line with the idea of inclusive theology and views that plurality is a reality that must be accepted absolutely.